An economic valuation of Marikina City library using revealed preference methods - Obal, Manilyn R. (2015)
To address the increasing demand for public libraries to redefine their values and justify their existence in this Digital Age, this study focused on one of the public libraries in the Philippines, Marikina City Library (MCL) and the estimation of its Total Economic Value (TEV) - the sum of the use and non-use benefits, expressed in monetary terms, that a person or a group of person could get from the direct, indirect use or non-usage of certain goods or services. TEV of MCL was estimated using an economic-value measurement model that was adapted based on Revealed Preference Theory, which asserts that a person's preferences can be deduced from his or her behavior and actual choices.